(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The igadget iis idesigned ithe iusage iof ithe ipython icoding ilanguage. iThe imonitored ivalues imay ibe iaccessed ifrom ithe iInternet iof iThings iplatform. iThe iair ipollutants iparameters iare itaken ifrom ithe ilow icost igas isensors. iThe iparameters iconsist iof: iconcentrations iof ismoke, icarbon imonoxide iand initrogen-di-oxide, itemperature iand ihumidity. iAlso ian ialarm iis itriggered ito isignify ihigh iconcentrations iof iemissions. iThis iacts ias ia iwarning ito ithe igovernment iabout ithe iair ipollution iprice. iA igraph iis iplotted iusing ithe imonitored ivalues ithe iusage iof iThing ispeak iplatform.